Application of AHP and DEMATEL Procedure on Brand Experience - Suddin Lada; Joehan Joehari William; Azaze-Azizi Abdul Adis (2020)
Brand experience comprises of numerous dimensions, attributes, and intangible components which are difficult to measure accurately. Hence, this paper proposes a hybrid multi-criteria decision making procedure, combining the analytical hierarchy process (AHP) and decision making trial and evaluation laboratory (DEMATEL) method to serve the decision-makers with a quantitative means of assessing the brand experience. AHP & DEMATEL helps capture both subjective and objective appraisal methods, offering a useful tool for evaluating evaluation accuracy and alternatives, thus eliminating bias in decisionmaking. Furthermore, conducting a thorough assessment to clearly define and understand which of these dimensions and attributes most impacts the brand and business is at least half the battle. It will make the task of building actionable strategies all the more manageable and more successful outcomes. The outputs of AHP and DEMATEL will certainly facilitate the decision-makers to make better-informed decisions concerning the brand experience.